La gimnasia formativa y el desarrollo de la lateralidad - Martínez Moreno, Adrián Mauricio (2017)
This researching was based on a problem that was aimed to strengthen laterality through the formative gymnastics in the students of the “Hermano Miguel Educative Unit" in Latacunga Canton because of there were students who did not develop correctly the activities directed by the teacher in the class of Physical Education, these students had flaws in motor coordination, the unbalance in their movements in the teaching learning process, capturing and producing several sounds according to the actions used, The methods used were quantitative and qualitative and the Technique was a pre-test that helped to compile researching information that allowed us to establish activities such as games and variety of exercises to help students strengthening their lateral development, motor development, and socio-affective interrelation among classmates and obtaining results through a test applied, in order to know the degrees of difficulties and mistakes that they have in the learning process....